Nostalgia : when are we ever at home? - Barbara Cassin (Fordham University press, 2016)
"Nostalgia makes claims on us both as individuals and as members of a political community. In this short book, Barbara Cassin provides an eloquent and sophisticated treatment of exile and of desire for a homeland, while showing how it has been possible for many to reimagine home in terms of language rather than territory. Moving from Homer's and Virgil's foundational accounts of nostalgia to the exilic writings of Hannah Arendt, Cassin revisits the dangerous implications of nostalgia for land and homeland, thinking them anew through questions of exile and language. Ultimately, Cassin shows how contemporary philosophy opens up the political stakes of rootedness and uprootedness, belonging and foreignness, helping us to reimagine our relations to others in a global and plurilingual world"--